2023
DOI: 10.3390/separations10060340
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Assessment of Therapeutic Phytoconstituents of Catharanthus roseus through GC-MS Analysis

Abstract: The leaves of Catharanthus roseus (L.) G. Don contain a large number of diverse secondary metabolites, making them comparably complex. The Catharanthus genus has received increased interest from scientists in recent years due to its extensive applications in several domains, including the pharmaceutical sector, where precise characterization of its characteristics is required. An effective inquiry technique is needed for chemo-profiling to identify the metabolites in plant samples. The main goal of this resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The GCMS analysis revealed that the CFEA contains numerous phytochemicals with beneficial biological effects. Some of these substances have been identified as having antimicrobial, antioxidant, and anti-inflammatory properties, including hexanoic acid, 2-ethyl anhydride, n-Hexadecanoic acid ( Thakur et al, 2018 ), glycerol 1,2-diacetate, Hexadecanoic acid ( El-Sayed et al, 2023 ), 1,2,3-Propanetriol, 1-acetate, benzofuran, 2,3-dihydro- ( Rani et al, 2023 ), 3-hydroxy-methyl ester ( Kumar et al, 2021 ), isopropyl hexacosyl ether, and 5-Hydroxymethyl-2-furaldehyde ( Fitriaturosidah et al, 2022 ). Additionally, phenol, 2,4-bis (1,1-dimethyl ethyl)-, has been found to have antifungal and biofilm-rupturing capabilities ( Sharaf, 2020 ), while D-Glucitol, 1,4-anhydro-, has antiophidic effects ( Singh et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The GCMS analysis revealed that the CFEA contains numerous phytochemicals with beneficial biological effects. Some of these substances have been identified as having antimicrobial, antioxidant, and anti-inflammatory properties, including hexanoic acid, 2-ethyl anhydride, n-Hexadecanoic acid ( Thakur et al, 2018 ), glycerol 1,2-diacetate, Hexadecanoic acid ( El-Sayed et al, 2023 ), 1,2,3-Propanetriol, 1-acetate, benzofuran, 2,3-dihydro- ( Rani et al, 2023 ), 3-hydroxy-methyl ester ( Kumar et al, 2021 ), isopropyl hexacosyl ether, and 5-Hydroxymethyl-2-furaldehyde ( Fitriaturosidah et al, 2022 ). Additionally, phenol, 2,4-bis (1,1-dimethyl ethyl)-, has been found to have antifungal and biofilm-rupturing capabilities ( Sharaf, 2020 ), while D-Glucitol, 1,4-anhydro-, has antiophidic effects ( Singh et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported previously about the health-promoting properties of bioactive compounds such as polyphenols, favonoids, tannins, etc. [91][92][93][94]. In a recent study, mangiferin (C-glucosylxanthone), a natural compound from mango, has been found to have a chemoprotective mechanism against colonic aberrant crypt foci (ACF) in rats by lowering ACF values and less colon tissue penetration induced by azoxymethane [86].…”
Section: Efect Of Mpp On the Antioxidant Potential Of The Probioticmentioning
confidence: 99%
“…Plant secondary metabolites may be qualitatively and quantitatively characterized using contemporary analytical methods such as spectrophotometry, high-performance liquid chromatography (HPLC), and gas-chromatography mass spectrometry (GC-MS) (Rani et al, 2023). While HPLC enables the simultaneous evaluation of antioxidant chemicals, spectrophotometry may be used to evaluate phenolics, flavonoids, saponins, and alkaloids.…”
Section: Analytical Techniquesmentioning
confidence: 99%